International health experiences in postgraduate medical education: A meta-analysis of their effect on graduates’ clinical practice among underserved populations - Dawe, Russell; McKelvie, Mark (Canadian Medical Education Journal, 2020)
Background: International health experiences (IHEs) are popular among medical learners and provide a valuable learning experience. IHE participants have demonstrated an increased intention to care for underserved populations in the future, but what is its actual impact on practice? This study evaluates the effect of postgraduate IHE participation on the future careers of clinicians regarding their work among underserved populations. Methods: We conducted a systematic review and meta-analysis of peer-reviewed articles comparing the populations served by physicians who had participated in an IHE with those of physicians who had not participated in an IHE. Results: 764 titles were scanned, 28 articles were reviewed, with an eventual 3 studies of fair-good or good quality identified. These addressed physicians’ service to domestic underserved populations, and also addressed future service in a low- or middle-income country (LMIC). Meta-analysis demonstrated a statistically-significant increase in service by IHE graduates to domestic underserved populations (OR = 2.12; CI = 95%; P = 0.03). The certainty of the evidence was low due to limitations in study design (non-randomised studies) and inconsistency in effects. Conclusion: Participation in an IHE may cause an increase in care for domestic underserved populations in future clinical practice, though further research from high quality randomised trials is needed to increase the certainty of the effect. Further study is needed to establish whether there is a similar effect with increased future service in a LMIC setting